PENGARUH STRATEGI PELAYANAN OUTLET DAN HUBUNGAN DENGAN OUTLET TERHADAP KINERJA SELLING-IN SERTA DAMPAKNYA TERHADAP KINERJA PEMASARAN (Studi : Outlet yang menjual Memory Card Sandisk di Semarang) - Kustriantomo, Fajar; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2015)
A good marketing performance showed a high level of sales, increasing the number of sales both in units of the product or in monetary units. The improved marketing performance marked also with good sales growth from year to year and higher growth than similar competitors and has a broad customer compared to previous years. This study aimed to analyze the influence of strategy and service outlets and outlet connection with the performance of selling-in and impact on the performance of marketingThis study uses multiple linear regression analysis using SPSS. The population used is the customer's customer Buana Gemilang Creatindo Semarang in January-August 2014. The samples used were 100 people with sample selection techniques using non- probability sampling accidental samplingThe results show that the strategy of influence on the performance and service outlets selling-in, relationships affect the performance of outlets selling-in, service strategy affect the performance of marketing outlets, outlets Relations affect the performance of selling-in, Performance selling-in effect on the performance of marketing, strategy service outlets and outlet connection directly influence the performance of marketing through selling-in performance.